2012
DOI: 10.1038/ijos.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

The photodynamic therapy on Streptococcus mutans biofilms using erythrosine and dental halogen curing unit

Abstract: The purpose of our study was to evaluate the effect of photodynamic therapy (PDT), using erythrosine as a photosensitizing agent and a dental halogen curing unit as a light source, on Streptococcus mutans in a biofilm phase. The S. mutans biofilms were formed in a 24-well cell culture cluster. Test groups consisted of biofilms divided into four groups: group 1: no photosensitizer or light irradiation treatment (control group); group 2: photosensitizer treatment alone; group 3: light irradiation alone; group 4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 24 publications
4
37
0
2
Order By: Relevance
“…This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012). In our study, the addition of erythrosine B did cause some reduction in malodour; however, this reduction was not statistically significant.…”
Section: Discussionsupporting
confidence: 52%
“…This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005). Various studies have reported that using the colourant erythrosine B as a photosensitizer enhances the antimicrobial properties of blue light from light-emitting diode (LED) or halogen light sources (De Lucca et al, 2012;Lee et al, 2012). In our study, the addition of erythrosine B did cause some reduction in malodour; however, this reduction was not statistically significant.…”
Section: Discussionsupporting
confidence: 52%
“…The relative high susceptibility of cariogenic bacteria, such as S. mutans and L. acidophilus, to PACT using a diverse collection of photosensitizers and light sources is adequately documented [23][24][25]. Others have examined the effectiveness of PACT with TBO associated to a LED as light source and innumerous investigations have shown great bacterial reduction (log reduction up to 5) or even the fully elimination of, when these bacteria are suspended in planktonic cultures [8,26] or organized in in vitro biofilms [11,26].…”
Section: Discussionmentioning
confidence: 97%
“…However, possibly because of the limitation of light penetration and drug diffusion, microorganisms were less affected in the biofilm phase than the planktonic counterparts (references). Moreover, Lee et al [43] were able to achieve significant cell death using erythrosine as a photosensitizing agent and a dental halogen light on S. mutans biofilm. Nevertheless, for dental use, several aspects, including energy, light irradiation times, and distance to the targeted area, must be carefully analyzed, aiming at tissue-tolerable temperature in the dentin, pulp, and other oral tissues.…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%